CRISPR-Cas9-mediated reactivation of the uricase pseudogene in human cells prevents acute hyperuricemia - Lais de Lima Balico; Eric A. Gaucher (Elsevier, 2021)
The utility of CRISPR-Cas9 to repair or reverse diseased states that arise from recent genetic mutations in the human genome is now widely appreciated. The use of CRISPR to "design" the outcomes of biology is challenged by both specialized ethicists and the general public. Less of a focus, however, is the ability of CRISPR to provide metabolic supplements or prophylactic molecules that improve long-term human health by overwriting ancient evolutionary events. Here, we use CRISPR to genomically integrate a functional uricase gene that encodes an enzymatically active protein into the human genome. These uricase-producing cells are able to reduce or even eliminate high concentrations of exogenous uric acid despite the enzyme being localized to peroxisomes. Our evolutionary engineered cells represent the first instance of the primate ape lineage expressing a functional uricase encoded in the genome within the last 20 million years. We anticipate that human cells expressing uricase will help prevent hyperuricemia (including gout) as well as hypertension and will help protect against fatty liver disease in the future.